Effects of Atorvastatin on Lipid Profiles and CETP (Cholesteryl Ester Transfer Protein) Levels in Pediatric Patients with Refractory Nephrotic Syndrome - Marizki Pondawinata; Yulistiani; Ninik Asmaningsih (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2025)
Atorvastatin is one of the statin groups indicated for curing and healing in pediatric with hyperlipidemia because it has high potential and safe with  less drug side effects. Several studies have reported the impact of atorvastatin on CETP levels, however the findings remain inconclusive. This study aimed to assess the effect of atorvastatin on lipid profiles and CETP levels in pediatrics patients with refractory nephrotic syndrome and hyperlipidemia. A double-blind, randomized clinical trial (RCT) using pre- and post- test design was conducted over for 4 weeks, involving the treatment group (atorvastatin) and the control group (placebo). The research took place at the pediatric nephrology outpatient clinic of Dr. Soetomo Hospital from December 2019 to March 2020. Baseline assessments at week 0 included measurements of total cholesterol, LDL, HDL, TG, CETP, and other laboratory parameters. Follow-up testing was performed after 4 weeks. The difference in average total cholesterol and LDL at week 0 and week 4 in the control group and the treatment group was significant (p <0.05). Giving atorvastatin reduced total cholesterol (29.2%), LDL cholesterol (30.8%), TG level (7.5%), and did not yet have an increase in HDL cholesterol levels. The mean CETP level in the treatment group were not significant differences despite a decrease in CETP level of 8%. Patients giving atorvastatin showed a relationship between changes in CETP level with LDL level and total cholesterol. These findings suggest that atorvastatin significantly lowers total cholesterol, LDL, and CETP levels in pediatric refractory nephrotic syndrome with hyperlipidemia.